Diagnosis and treatment protocol for COVID‐19 patients (Trial Version 9) - Released by National Health Commission & National Administration of Traditional Chinese Medicine on March 15, 2022 (Wiley, 2022)
Abstract To further improve the diagnosis and treatment of COVID‐19, China National Health Commission and the National Administration of Traditional Chinese Medicine convened a group of experts to revise the relevant content of the Diagnosis and Treatment Protocol for COVID‐19 Patients (Trial Version 8) and developed the Diagnosis and Treatment Protocol for COVID‐19 Patients (Trial Version 9), summarizing the etiological characteristics, epidemiological characteristics, pathological changes, clinical features, diagnosis, clinical classification, population with high risk of severe/critical illnesses, early warning predictors for severe/critical illnesses, differential diagnosis, case identification and reporting, treatment, nursing, discharge criteria and precautions after discharge, patient transfer, control of nosocomial infection in medical institutions, and disease prevention.